Collagen fragment biomarkers as serological biomarkers of lean body mass – a biomarker pilot study from the DAHANCA25B cohort and matched controls. Issue 4 (22nd April 2015) - Nedergaard, Anders; Dalgas, Ulrik; Primdahl, Hanne; Johansen, Jørgen; Overgaard, Jens; Overgaard, Kristian; Henriksen, Kim; Karsdal, Morten Asser; Lønbro, Simon
Abstract: Background: Loss of muscle mass and function is an important complication to ageing and a range of pathologies, including, but not restricted to, cancer, organ failures, and sepsis. A number of interventions have been proposed ranging from exercise to anabolic pharmacological therapy, with varying success. Easily applicable serological biomarkers of lean and/or muscle mass and change therein would benefit monitoring of muscle mass during muscle atrophy as well as during recovery. We set out to validate if novel peptide biomarkers derived from Collagen III and VI were markers of lean body mass (LBM) or change therein in head and neck cancer patients in the Danish Head and Neck Cancer Group(DAHANCA) 25B cohort subjected to resistance training as well as in an age‐matched and gender‐matched control group. Methods: Blood samples and dual X‐ray absorptiometry data were measured at baseline, after 12 and 24 weeks in 41 HNSCC subjects of the DAHANCA 25B cohort of subjects recovering from neck and head cancer (stages provided in Table  1), and at baseline only in 21 healthy age‐matched and gender‐matched controls. Serum from blood was analyzed for the ProC3, IC6, and C6M peptide biomarkers and LBM were derived from the dual X‐ray absorptiometry scans. Results: We were not able to show any correlation between biomarkers and LBM or C6M and anabolic response to exercise in recovering head and neck cancer patients. However, we did find that the biomarkers IC6, IC6/C6M, and ProC3 are biomarkers of LBM in the control group subjects ( R 2 / P of 0.249/0.035, 0.416/0.007 and 0.178 and P  = 0.057, respectively), Conclusion: In conclusion, the IC6, ProC3, and IC6/C6M biomarkers are indeed biomarkers of LBM in healthy individuals of both genders, but not in HNSCC patients.